The eviction due to precarious occupation in the light of the Fourth Civil Cassation Plenaries - Risco Sotil, Luis Felipe del (2016)
In this article the author show us the situation of the precarious along the eviction process where they are involved. Likewise, he tell us regarding the cumbersome situation and the null legal certainty that existed about this theme before the emission of the Fourth Civil Cassation Plenaries.After the Plenaries, the author points, were given rules to identify this matterand reach uniforms conclusions by judges, which represents an advance in the predictability of the judicial decisions about the eviction by precarious occupation.